2017
DOI: 10.1186/s12991-017-0150-6
|View full text |Cite
|
Sign up to set email alerts
|

Islam, mental health and law: a general overview

Abstract: Islam is the dominant religion in about 56 countries around the globe, and has more than 1.2 billion followers. Islam represents a holistic way of life, and according to a large proportion of its followers, the Islamic law or Shari’ah should prevail over secular law and should be implemented as state law. The etymological root of the word Shari’ah can be traced back to the harsh life in the desert and it means “pathway to be followed” or “path to the water hole,” since the water was the basic element and prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 21 publications
2
18
0
Order By: Relevance
“…Previous studies have already substantiated this strong positive connection between religion and mental health. It was concluded that psychiatry and religion were closely connected and religious beliefs support an individual to sustain one's life in different domains [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have already substantiated this strong positive connection between religion and mental health. It was concluded that psychiatry and religion were closely connected and religious beliefs support an individual to sustain one's life in different domains [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Religion is an important concept in mental health commonly used as coping strategy [ 27 ]. In this study Muslims were less likely to report symptoms of psychiatric morbidity, probably due to an underlining moral necessity for protection and care of the vulnerable individuals inherent within it [ 34 ]. Parental education influences children´s manner, actions and motivation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have already substantiated this strong positive connection between religion and mental health. It was concluded that psychiatry and religion were closely connected and religious beliefs support an individual to sustain one's life in different domains [23][24][25].…”
Section: Discussionmentioning
confidence: 99%